2004
DOI: 10.1002/jpln.200320368
|View full text |Cite
|
Sign up to set email alerts
|

The influence of phosphorus nutrition on the physiological response of moth bean genotypes to drought

Abstract: SummaryFour genotypes of moth bean (Vigna aconitifolia Jacq. Marechal), including two early (RMO-257 and CZM-18) and two late flowering types (CAZRI moth-1 and Jawala) were grown at two levels of phosphorus (0 and 40 kg ha ±1 ) and subjected to drought by withholding of water until wilting at the pre-flowering stage in a pot trial. Drought significantly decreased plant water potential, relative water content, rate of net photosynthesis, contents of chlorophyll, starch, soluble protein, and nitrate reductase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 30 publications
(27 reference statements)
8
58
0
Order By: Relevance
“…In addition, similar results have been also observed in Fargesia denudata Yi (Liu et al, 2014). Some studies have indicated that P application adaptively regulates the level of N metabolism by changing its correlative enzymes activities under water stress (Burman et al, , 2009Garg et al, 2004). Our studies found that P application exhibited minimal effects on NO À 3 reduction and NH þ 4 assimilation in well-watered dwarf bamboo (Table 4, Fig.…”
Section: Nitrogen Metabolismsupporting
confidence: 88%
See 3 more Smart Citations
“…In addition, similar results have been also observed in Fargesia denudata Yi (Liu et al, 2014). Some studies have indicated that P application adaptively regulates the level of N metabolism by changing its correlative enzymes activities under water stress (Burman et al, , 2009Garg et al, 2004). Our studies found that P application exhibited minimal effects on NO À 3 reduction and NH þ 4 assimilation in well-watered dwarf bamboo (Table 4, Fig.…”
Section: Nitrogen Metabolismsupporting
confidence: 88%
“…However, P application had minimal effect on LRWC of dwarf bamboo, regardless of water availability (Table 2), as also shown in previous studies of other crop species Singh et al, 2006b;Burman et al, 2009). Moreover, the LRWC of dwarf bamboo was influenced by water-P interaction (Table 6), which is due to interactive effects on leaf area Garg et al, 2004).…”
Section: Growth and Water Statussupporting
confidence: 77%
See 2 more Smart Citations
“…Thus, nutrient supply strongly affects crop productivity under drought conditions, but this is also very complex [8][9][10]. The positive effects of N and P on plant growth under drought conditions are attributed to an increase in water-use efficiency, stomatal conductance [11][12][13][14], photosynthesis and ATPase activity [5,15], as well as higher cell membrane stability and improved osmotic adjustment [16,17]. However, K increases a plant s drought tolerance through its functions in…”
Section: Introductionmentioning
confidence: 99%